Механизмы миграции кислорода в силициде титана Ti5Si3 - Чумакова, Лора Сергеевна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
In the present study, we performed the calculations of oxygen absorption energies in titanium silicide Ti5Si3 using the projector augmented-wave method within the density functional theory. The most stable positions for O in bulk compound were determined. The migration barriers between these positions were calculated that allowed us to determine the most preferable migration pathways.